An investigation into the growth and use of computer graphics and animation in Zimbabwe: present and future prospects - Mutsinze, Quinton (Midlands State University, 2017)
Computer graphics and animation has emerged as a strong competitor in the film making arena with the advent technical world Zimbabwe has also had a taste of the fast digitalised satellite television that is DSTV. Film making and television programming in Zimbabwe has also experienced an evolution with the introduction of satellite television in that most people are now accustomed to trendy genres to view. This study is mainly focusing on finding out whether or not computer graphics and animation are being used in film and television production to their full potential. The study is also aimed at tracing the development of Computer graphics and animation and predicts its future in the production of films in Zimbabwe. Currently the Zimbabwean film industry has little education facilities that teach computer graphics and animation, also television and film has grown to be less competitive and unappealing to the Zimbabwean audience and cannot compete with other Film and television Industries because of the advent of the use of computer graphics and animation in production.